Interplay between pi-bridges and positions of branched alkyl groups of unsymmetrical D-A-D-pi-A squaraines in dye-sensitized solar cells: mode of dye anchoring and the charge transfer process at the TiO2/Dye/electrolyte interface - Punitharasu, Vellimalai; Kavungathodi, Munavvar Fairoos Mele; Nithyanandhan, Jayaraj (ACS Applied Materials & Interfaces, 2017)
Far-red-absorbing squaraines possessing high molar absorptivity (>10(5) M-1 cm(-1)) are being attracted as high-efficiency chromophores in dye-sensitized solar cells (DSSCs). A series of donor acceptor -donor-pi spacer-acceptor (D-A-D-pi-A) unsymmetrical squaraines, PSQ1-5, with indoline donor and squaric/cyanoacetic acid acceptor units, were designed for sensitized solar cells. For extending the absorption toward the near-infrared region (NIR) and controlling the orientation on the TiO2 surface, benzene (PSQ1 and PSQ2) and thiophene (PSQ3-5) 7r-spacers and out-of-plane branched alkyl groups at the indoline that are away (PSQ1, PSQ3, and PSQS) or near (PSQ2 and PSQ4) the anchoring group, respectively, were introduced. Dynamic aggregation tendency of PSQ1 and PSQ3 than that of their isomers systematically modulates the orientation on the TiO2 surface, which in turn enhances photovoltaic performance. Absorptance on a thin transparent TiO2 film shows a visible-to-NIR response with an onset around 800 nm for PSQ3-5. Although there is resemblance in electrochemical redox levels, their high injection efficiency and recombination resistance differentiated impact on the way of anchoring and the dihedral angle between D-A-D units and g-spacers. DSSCs sensitized with PSQS achieved a PCE of 8.15% under simulated AM 1.5G illumination (100 mW cm(-2)), with the current density (j) and open-circuit voltage (Voc) of 19.73 mA cm(-2) and 630 mV, respectively. A clear comparison of the incident-photon-to-current conversion efficiency versus the light-harvesting efficiency correlates the structure-property relationship with J obtained for PSQ dyes. Electrochemical impedance spectroscopy was carried out to examine the TiO2/dye/electrolyte interface for further confirmation of the enhanced PCE of top-se-alkylated PSQS over that of other dyes.
Keywords: D-A-D-pi-A framework; dye-sensitized solar cell; H- and J-type aggregation; orientation of dyes; static/dynamic aggregates; unsymmetrical squaraine